Pengembangan Perekat Likuid dan Papan Partikel dari Limbah Tandan Kosong Sawit - Surdiding Ruhendi; Tito Sucipto (Institut Pertanian Bogor, 2013)
Oil palm empty fruit bunches (EFB) is one of lignocellulosic natural resource, which is highly potential as adhesive and particleboard raw materials. The purpose of the study was determine wood liquid qualities, and to evaluate the effect of adhesive contents, wood liquid extension levels on melamine formaldehyde (MF) resin, and resorcinol formaldehyde (RF) fortification levels on wood liquid to particleboard quality. The results showed that the EFB wood liquid is considered as phenolic resin group, liquid form and free of dirt, reddish brown color, pH 11, 34 cps viscosity, solids content of 34.47%, and gelatine time >60 minutes. Some characteristics of wood liquid adhesives meet SNI 06-4567-1998, namely the form, appearance, pH, and gelatine time. The physical and mechanical properties of particle board for all treatments were 0.64-0.93 g/cm3 density, moisture content 6-12%, thickness swelling 13-292%, water absorption 39-239%, modulus of rupture (MOR) 16-199 kg/cm2, modulus of elasticity (MOE) 2321-19810 kg/cm2, internal bonding 0.16-7.19 kg, and screw holding power 16-62 kg. Some physical and mechanical properties of particle board meet the standard of JIS A 5908-2003. Particleboard using MF resin without wood liquid extension (adhesive content of 20%) was the best quality particleboard. Wood liquid for particleboard recommended using wood liquid fortified with 5% MF resin (adhesive content of 15%) and MF resin with 15% wood liquid extensions (adhesive content of 20%) produced good quality particleboard.